2018
DOI: 10.1155/2018/3461572
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomics Study of Patients with Gout Using Gas Chromatography-Mass Spectrometry

Abstract: Objectives Gout is a common type of inflammatory arthritis. The aim of this study was to detect urinary metabolic changes in gout patients which may contribute to understanding the pathological mechanism of gout and discovering potential metabolite markers. Methods Urine samples from 35 gout patients and 29 healthy volunteers were analyzed by gas chromatography–mass spectrometry (GC–MS). Orthogonal partial least-squares discriminant analysis (OPLS-DA) was performed to screen differential metabolites between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Previous studies have consistently demonstrated the dysfunctional energy metabolism in patients with hyperuricemia as well as in animal models [ 22 , 24 26 ]. Important tricarboxylic acid (TCA) cycle intermediate metabolites such as succinate, citrate, and fumarate were downregulated in urine of gout patients and hyperuricemic mouse [ 27 , 28 ]. Hyperuricemic rats in our study exhibited an elevated level of β -glucose in serum together with a decreased level of succinate in urine as compared with normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently demonstrated the dysfunctional energy metabolism in patients with hyperuricemia as well as in animal models [ 22 , 24 26 ]. Important tricarboxylic acid (TCA) cycle intermediate metabolites such as succinate, citrate, and fumarate were downregulated in urine of gout patients and hyperuricemic mouse [ 27 , 28 ]. Hyperuricemic rats in our study exhibited an elevated level of β -glucose in serum together with a decreased level of succinate in urine as compared with normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of TBI commonly live with neurocognitive deficits and physical disability and increased risk of neurodegenerative disease in the long term (Pattinson and Gill, 2018). Unfortunately, no drug has been approved in Phase III of clinical trials for treating TBI (Stocchetti et al., 2015) because of complex pathogenesis, such as burst reactive oxygen species, increased glutamate levels, destroyed blood–brain barrier (BBB), uncontrolled neuroinflammation, and obliterated synapse (Li et al., 2018; Ma et al., 2018; Ichkova et al., 2019). Thus, the consensus of multitarget intervention was formed as its therapeutic principle.…”
mentioning
confidence: 99%
“…In the past, the diagnosis of MADD could be quickly and easily achieved using tandem mass spectrometry of blood samples, which could be further confirmed by gas chromatography mass spectrometry analysis of urine organic acids ( 21 , 22 ). However, in late-onset patients, the increased levels of acylcarnitines and urinary organic acids may be mild and atypical, or detectable only during acute episodes ( 5 , 17 ), therefore, genetic analysis to detect mutations in the ETF or ETFDH genes is considered as the key method for a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%